Changes in male reproductive health and effects of endocrine disruptors in Scandinavian countries Alterações na saúde reprodutiva masculina e efeitos dos desreguladores endócrinos nos países escandinavos - Jorma Toppari; Anne-Maarit Haavisto; Markku Alanen (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
Male reproductive health has deteriorated in many ways during the last decades. The incidence of testicular cancer has rapidly increased in Europe and European-derived populations. Sperm concentrations have declined and sperm motility and morphology have worsened in many areas. Both adverse trends have been shown to be associated with year of birth. Older birth cohorts have better reproductive health than the younger generations. Incidences of cryptorchidism and hypospadias have also increased according to several studies. The reasons for secular trends are unknown, but the rapid pace of the change points to environmental causes. Endocrine disrupting chemicals have been hypothesized to influence male reproductive health. A saúde reprodutiva masculina tem-se deteriorado de diversas maneiras nas últimas décadas. A incidência do câncer de testículo aumentou rapidamente na Europa e nas populações descendentes de europeus. A concentração de espermatozóides tem decaído, e a motilidade e morfologia têm piorado em muitas regiões. Ambas tendências adversas foram correlacionadas ao ano de nascimento. As coortes mais velhas apresentam melhor saúde reprodutiva do que as gerações mais jovens. De acordo com vários estudos, as incidências de criptorquidia e de hipospadia vêm aumentando. Não se conhecem os fatores envolvidos nessas tendências, mas a velocidade da mudança sugere alterações ambientais. Foi levantada a hipótese da influência dos desreguladores endócrinos sobre a saúde reprodutiva masculina.